-114=3(6r-6)-6r

Simple and best practice solution for -114=3(6r-6)-6r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -114=3(6r-6)-6r equation:



-114=3(6r-6)-6r
We move all terms to the left:
-114-(3(6r-6)-6r)=0
We calculate terms in parentheses: -(3(6r-6)-6r), so:
3(6r-6)-6r
We add all the numbers together, and all the variables
-6r+3(6r-6)
We multiply parentheses
-6r+18r-18
We add all the numbers together, and all the variables
12r-18
Back to the equation:
-(12r-18)
We get rid of parentheses
-12r+18-114=0
We add all the numbers together, and all the variables
-12r-96=0
We move all terms containing r to the left, all other terms to the right
-12r=96
r=96/-12
r=-8

See similar equations:

| 10x=2(x-5)=25 | | 0=4x+5/x-9 | | 1000+1200x=1175x+1500 | | 10=15y-6 | | 15x-25=95-5x | | 25*n=20 | | 25*n=30 | | H(t)=3t^2-4 | | 5.02+1.03x=13 | | 12000=15000/x | | 0=-4.9x^2+40x-7 | | 140=70/x | | 10x-7=7x+32 | | -90=-k-9 | | (5x-17)=(2x+50)=180 | | -14=r+1 | | 15=j-1 | | 5=t+5 | | -19=6z-1 | | 1/3x-15=x-1 | | 3(2x-2)+x+5=-10+10 | | -14=-n+1 | | 1/3x-15=x1 | | 11=x-3(x-9) | | 5x-22+19+3x=x+32-4x-8.6 | | 1/3x+6=1/2x+2 | | 15s^2+4s-4=0 | | 2006-1.7x=5.4 | | 4(e+11=48 | | 10a+3=-4 | | 35-2/x=14 | | X/3=3x+1 |

Equations solver categories